2018
DOI: 10.2174/1871520617666171113121246
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Polysaccharides as An Anti-cancer Agent

Abstract: The mushroom Ganoderma lucidum (G. lucidum) has been used for centuries in Asian countries to treat various diseases and to promote health and longevity. Clinical studies have shown beneficial effects of G. lucidum as an alternative adjuvant therapy in cancer patients without obvious toxicity. G. lucidum polysaccharides (GLP) is the main bioactive component in the water soluble extracts of this mushroom. Evidence from in vitro and in vivo studies has demonstrated that GLP possesses potential anticancer activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 76 publications
(111 reference statements)
1
75
0
7
Order By: Relevance
“…These results indicated that animals treated with G. Lucidum cause a significant increase in the levels of antioxidant enzymes. These results are in line with the reports of other researchers that allude to the fact that Gandoderma lucidium has antioxidant activities both in vivo and in vitro [ 45 , 46 , 47 ]. These results indicated the hepatoprotective efficacy of G. Lucidum.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that animals treated with G. Lucidum cause a significant increase in the levels of antioxidant enzymes. These results are in line with the reports of other researchers that allude to the fact that Gandoderma lucidium has antioxidant activities both in vivo and in vitro [ 45 , 46 , 47 ]. These results indicated the hepatoprotective efficacy of G. Lucidum.…”
Section: Discussionsupporting
confidence: 93%
“…GL has been used in the treatment of various diseases, such as allergy, arthritis, bronchitis, gastric ulcer, hyperglycemia, hypertension, chronic hepatitis, insomnia, nephritis, nerve weakness, inflammation, and cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence of prebiotic activity on the microbiota, although this could be secondary to a direct effect on immune system components. Its powerful immunomodulatory effects led to extend its field of use also to the therapy of tumors, a topic which, however, goes beyond the themes of this chapter [138]. In DSS-induced colitis in rats, G. lucidum β-glucans increased SCFA-producing bacteria such as Ruminococcus, and reduced pathobionts such as Escherichia and Shigella in both the small intestine and cecum [139].…”
Section: Microbiota-modulating Fungimentioning
confidence: 99%